Phytoseiidae (Acari: Mesostigmata) from natural ecosystems in the State of São Paulo, Brazil - de Moraes, Gilberto José; Barbosa, Marina Ferraz De Camargo; de Castro, Tatiane Marie Martins Gomes (Zootaxa, 2013)
This work describes the results of a study of the phytoseiid mites collected from plants in two natural ecosystems in the State of São Paulo, Brazil—Cerrado and Atlantic Forest. In this study, 40 phytoseiid species are reported. Measurements of different structures are given for species for which measurements for the respective São Paulo populations were not previously provided. This study also includes the description of two new genera, Breviseius g. n. and Serraseius g. n., and ten new species, Amblydromalus macroatrium n. sp., Amblyseius atlanticus n. sp., Breviseius sennae n. sp., Cocoseius paucisetis n. sp., Proprioseiospsis pariquerassuensis n. sp., Serraseius caicara n. sp., Typhlodromalus ingae n. sp., Typhlodromalus feresisimilis n. sp., Typhlodromips corniformis n. sp. and Typhlodromips robustisetus n. sp..